Construction of bioactive nanocomposites from beta-sitosterol, fucoidan, chitosan, and silver nanoparticles for anticancer applications - Tayel, Ahmed A.; Elagezy, Fatma K.; Abdella, Asmaa; Gad, Hend A.; El-Hefnawy, Mohamed E.; Alhayyani, Sultan; El-Far, Shaymaa W. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCancers (e.g., colon and skin cancers) are significant causes of mortality. We developed novel anticancer nanocomposites comprising natural bioactive compounds and metal nanoparticles, involving conjugation of beta-sitosterol (BSt) and fucoidan (Fu), for biogenic synthesis of silver nanoparticles (AgNPs), before conjugation with chitosan (CS), to generate potential innovative anticancerous nanocomposites.MethodsThe fabricated Fu/BSt/AgNPs/CS nanocomposites were characterized for efficacy against colon cancer (HCT-116) and skin cancer (A375) cells. Electron microscopy (SEM and TEM), FTIR infrared spectroscopy, DLS analysis and UV-Vis spectroscopy, confirmed the synthesis and interactions within nanocomposites. The MTT assay and dual staining validated the potential nanocomposites’ actions as anticancerous materials, compared to “cisplatin”.Results and discussionAgNPs had a mean diameter of 8.83 nm, whereas Fu/BSt/AgNPs/CS had 146.6 nm size. MTT assay revealed that IC50 of Fu/BSt/AgNPs and Fu/BSt/AgNPs/CS nanocomposites were 16.23, 12.75 mg/L against HCT-116 cells, and 34.81, 22.44 mg/L against A375 cells, respectively, which significantly exceeded the cisplatin IC50 (25.56 and 79.77, respectively). The cancer cells’ treatment with nanocomposites revealed significant apoptosis induction and cell growth inhibition. Ultra-structural imaging confirmed the nanocomposites’ ability to trigger cancer cells to undergo morphological alterations, destructions and collapse. Invented Fu/BSt/AgNPs/CS nanocomposites have great promises as safe and effective treatments for colon and skin cancers, generated from natural compounds.